2015
DOI: 10.3109/0284186x.2015.1068445
|View full text |Cite
|
Sign up to set email alerts
|

Impact of early disease progression and surgical complications on adjuvant chemotherapy completion rates and survival in patients undergoing the surgery first approach for resectable pancreatic ductal adenocarcinoma – A population-based cohort study

Abstract: Gladhaug (2016) Impact of early disease progression and surgical complications on adjuvant chemotherapy completion rates and survival in patients undergoing the surgery first approach for resectable pancreatic ductal adenocarcinoma -A population-based cohort study, Acta Oncologica, 55:3,[265][266][267][268][269][270][271][272][273][274][275][276][277] DOI: 10.3109 conclusions. MMT completion is strongly associated with reduced mortality risk in patients with resectable PDAC undergoing the SF approach. Early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(102 citation statements)
references
References 39 publications
2
98
2
Order By: Relevance
“…A recent study reported a median survival of 29·7 months for patients who underwent pancreatoduodenectomy with venous resection and received adjuvant chemotherapy. This is considerably better than results from other centres, in which median survival rates ranged from 15 to 25 months following venous resection for pancreatic cancer. Interestingly, Murakami and colleagues reported a very high frequency of patients undergoing venous resection during pancreatoduodenectomy in their study population (46·6 per cent of those included); however, only 60 per cent of the patients had true tumour invasion of the superior mesenteric–portal vein wall.…”
Section: Discussionmentioning
confidence: 67%
“…A recent study reported a median survival of 29·7 months for patients who underwent pancreatoduodenectomy with venous resection and received adjuvant chemotherapy. This is considerably better than results from other centres, in which median survival rates ranged from 15 to 25 months following venous resection for pancreatic cancer. Interestingly, Murakami and colleagues reported a very high frequency of patients undergoing venous resection during pancreatoduodenectomy in their study population (46·6 per cent of those included); however, only 60 per cent of the patients had true tumour invasion of the superior mesenteric–portal vein wall.…”
Section: Discussionmentioning
confidence: 67%
“…5,6 Morbidity after surgery is not uncommon in elderly patients and may cause omission of chemotherapy. 25,26,35 Unfortunately, these data were not available in the present study. No distinction was made between neo-and adjuvant chemotherapy because NOR did not provide this.…”
Section: Discussionmentioning
confidence: 89%
“…Neoadjuvant chemotherapy has been advocated in patients with resectable tumors to secure completion of systemic treatment[15] which may be precluded by postoperative complications or early disease progression after upfront surgery[16]. The net result of neoadjuvance is selection of patients with favorable tumor biology for subsequent resection.…”
Section: Primary Resectable Tumorsmentioning
confidence: 99%